2021
DOI: 10.1002/ajp.23262
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the survival of wild cotton‐top tamarin (Saguinus oedipus) infants

Abstract: Studies of cooperative breeding species have suggested that helpers are needed for infant survival and that helpers gain skills to successfully raise their own offspring.Studies of callitrichids in managed care and early field studies suggested that group size correlated with infant survival and that helpers needed to learn parental skills to be successful breeders. We present infant survival data from a 20-year field study of cotton-top tamarins (Saguinus oedipus) in Colombia involving 126 litters born to 41 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…As is typical for most callitrichids born in the wild or in managed care (Bales et al, 2001;Dietz et al, 1994;Goldizen, Terborgh, et al, 1988;Savage et al, , 2009Savage et al, , 2021, this study found that twins were most common, followed by singletons and triplets. Singletons, twins, and triplets all have similar seasonal patterns of birth timing.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…As is typical for most callitrichids born in the wild or in managed care (Bales et al, 2001;Dietz et al, 1994;Goldizen, Terborgh, et al, 1988;Savage et al, , 2009Savage et al, , 2021, this study found that twins were most common, followed by singletons and triplets. Singletons, twins, and triplets all have similar seasonal patterns of birth timing.…”
Section: Discussionmentioning
confidence: 51%
“…Infants born during the seasonal peak (April-August) had a greater probability of surviving to 6 months of age than those infants born off-peak (September-March) regardless of the number of helpers (Savage et al, 2021). This suggests that females have undergone ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We would like to note some potential limitations to this study. First, we compiled data from zoos and biomedical laboratories, settings in which husbandry mitigates many perinatal risks, including predators, infection, intraspecific aggression ( Savage et al., 2021 ), and environmental stressors. Many of the species studied herein breed seasonally in the wild but more regularly in captivity (with artificial light cycles and constant humidity/food availability).…”
Section: Discussionmentioning
confidence: 99%